Privatisation in European Ports. Final Report of the NEW EPOC Project ,,Structural Change in Port Economies“ - Rainer Dombois; Anja Koutsoutos (Institut Arbeit und Wirtschaft (IAW), Universität Bremen und Arbeitnehmerkammer Bremen, 2007)
Seaports nowadays are acting under a common set of constraints. They are players in a globalised and competitive industry, the logistics industry. With intense territorial roots, they are exposed to strong competitive pressures from the global shipping companies and their alliances on the one hand and from competing seaports and increasingly from multinational harbour companies, on the other. Operating in a globalised economy and a European political common context NEW EPOC seaports in their strategies are shaped by specific local conditions. Ports differ one from the other by traditions, institutional and administrative structures, relations with the hinterland, competitive position etc.and so do their strategic choices. Privatisation is a common tendency in all NEW EPOC ports though patterns are varying. It has opened new strategic spaces but created new problems as well - like employment and environmental problems. A major challenge brought up by privatisation is the growing need for cooperation and coordination between different actors and diverging interests. – – Lokale Häfen sind Akteure in einem hochgradig globalisierten Wirtschaftszweig, der Logistikindustrie. Territorial tief verwurzelt, sind sie einem starken Wettbewerbsdruck seitens globaler Schiffahrtsunternehmen einerseits, anderer Häfen und zunehmend auch multinationaler Hafenunternehmen andererseits ausgesetzt. NEW EPOC-Häfen operieren im Kontext einer globalisierten Ökonomie und im Rahmen der Europäischen Union, ihre Strategien werden aber in hohem Maße durch spezifische lokale und nationale Bedingungen geprägt. Häfen unterscheiden sich in ihren Traditionen, ihren institutionellen und administrativen Strukturen, Beziehungen zum Hinterland, Wettbewerbsposition etc. und so auch in ihren strategischen Optionen. Privatisierung ist eine gemeinsame Tendenz in allen NEW EPOC-Häfen; allerdings zeigen die Muster eine große Variationsbreite auf. Privatisierung hat neue strategische Räume eröffnet, aber auch neue Probleme geschaffen - so vor allem für den Arbeitsmarkt und die Umwelt. Zunehmende Bedeutung hat auch die Kooperation und Koordination vielfältiger Akteure mit divergierenden Interessenlagen gewonnen.
Keywords: 330; Hafen; Privatisierung; Hafenpolitik; EU-Staaten